2021
DOI: 10.1017/s0272263121000127
|View full text |Cite
|
Sign up to set email alerts
|

The Reliability and Validity of Procedural Memory Assessments Used in Second Language Acquisition Research

Abstract: Evidence for the role of procedural memory in second language (L2) acquisition has emerged in our field. However, little is known about the reliability and validity of the procedural memory measures used in this research. The present study (N = 119) examined the reliability and the convergent and discriminant validity of three assessments that have previously been used to examine procedural memory learning ability in L2 acquisition, the dual-task Weather Prediction Task (DT-WPT), the Alternating Serial Reactio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(49 citation statements)
references
References 70 publications
3
44
0
Order By: Relevance
“…Since the majority of studies focus on learning performance that can be assessed in a single session, assessing internal consistency is preferred over test-retest reliability. Buffington et al (2021) also administered multiple experimental tasks to a group of 99 subjects, including the ASRT task, and calculated split-half reliability. The Spearman-Brown split-half reliability of ASRT was found to be only a moderate .42.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the majority of studies focus on learning performance that can be assessed in a single session, assessing internal consistency is preferred over test-retest reliability. Buffington et al (2021) also administered multiple experimental tasks to a group of 99 subjects, including the ASRT task, and calculated split-half reliability. The Spearman-Brown split-half reliability of ASRT was found to be only a moderate .42.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the learning score based on pattern-random difference likely underestimates the true learning that occurs in the task. Furthermore, unlike Buffington et al (2021), we excluded trials that were repetitions (e.g., 222) or trills (e.g., 232), as subjects likely have pre-existing response tendencies to such trials (Soetens et al, 2004). This also possibly increased the robustness of our learning scores.…”
Section: Discussionmentioning
confidence: 99%
“…More research is needed to investigate the complex relationships between these factors. The role of cognitive and linguistic individual differences, is clearly a burgeoning area of interest in the language learning sciences (e.g., Bolibaugh & Foster, 2021;Buffington et al, 2021;Pili-Moss, 2021;Riches & Jackson, 2018;Walker et al, 2020; including special issues dedicated to the topic such as those edited by Andringa & Dąbrowska, 2019;Roberts & Meyer, 2012), and investigating the role of individual cognitive abilities in prediction and, specifically, error-based learning, in L1 and L2 (or Lx) speakers would constitute a timely extension of this agenda. Such research could shed more light on some of the factors we have reviewed, such as the varying effect of L2 proficiency (e.g., helping to clarify the relative contributions of knowledge representation and "procedural" proficiency in enabling prediction).…”
Section: Discussionmentioning
confidence: 99%
“…Procedural learning ability was indexed by performance on an alternate serial reaction time task adapted from a previously employed serial reaction time paradigm [ 40 ]. Previous studies investigating the reliability of this task have found a test-retest r = .45 [ 41 ], Cronbach α values between .75 and .79 (RT scores) and between .69 and .75 (accuracy scores) [ 42 ], as well as a Spearman-Brown split-half reliability index of .42 [ 25 ]. Participants saw four squares arranged in a diamond shape configuration on screen and were asked to immediately react to the changes in the position of a smiley by pressing the corresponding buttons on a game controller.…”
Section: Methodsmentioning
confidence: 99%
“…Overall the results of these studies have converged in finding that declarative learning abilities (assessed via behavioural verbal and visual declarative memory measures) tended to positively predict learning of morphosyntax at early stages of exposure (see also Hamrick [ 24 ] for similar results obtained using a different artificial language paradigm). However, after extended exposure (or after periods of no exposure [ 24 ]) morphosyntactic learning (particularly word order) became positively related to learners’ procedural learning ability measured by probabilistic learning tasks or implicit sequence learning tasks [ 21 – 23 , 25 ].…”
Section: Introductionmentioning
confidence: 99%